Regulatory Coherence and Accountability in Indonesia’s National Health Insurance: A Doctrinal and Stakeholder Analysis - Nurul Istiqomah; Izza Mafruhah; Norlida Hanim Mohd Saleh; Dewi Ismoyowati; Alif Ksatria Firdausi AI (Unissula, 2026)
This article examines the regulatory coherence and accountability of Indonesia’s National Health Insurance (JKN) within the framework of constitutional and administrative law. It addresses two principal legal questions: whether the JKN regulatory structure demonstrates hierarchical consistency within Indonesia’s system of laws, and whether its governance design particularly in relation to the referral system and the arrears regime complies with principles of legal certainty, proportionality, and accountability. Using a doctrinal legal approach supported by stakeholder mapping through the MACTOR framework, the study evaluates both normative structure and institutional interaction. The findings indicate that the JKN framework is formally consistent with constitutional mandates and statutory delegation under the SJSN Law and the BPJS Law. However, horizontal regulatory harmonization remains incomplete, particularly regarding the interaction between hospital classification regulations and BPJS referral policies. Moreover, the arrears enforcement mechanism, while legally grounded in mandatory participation, lacks sufficiently clear criteria to distinguish inability to pay from non-compliance. The study concludes that targeted amendments to implementing regulations and the establishment of formal administrative dispute-resolution mechanisms are necessary to strengthen proportional enforcement, regulatory coherence, and institutional accountability within the JKN system.